Value Relevance of Consolidated Versus Parent Company Financial Statements: Evidence from the Largest Three European Capital Markets - Victor-Octavian Muller (Journal of Accounting and Management Information Systems (JAMIS), 2011)
Within the European Union, parent companies have to prepare and publish both consolidated and individual financial statements. The objective of financial statements with general purpose is to give information regarding the financial position, performance and changes in financial position of the reporting entity, information that is useful to investors and other users in making economic decisions. In order to be useful, financial information needs to be relevant to the decision-making process of users in general, and investors in particular. Therefore, the following question arises naturally – which of the two sets best serves the information needs of investors (and other categories of users), respectively which of the two sets is more relevant for investors? In our scientific endeavor we set to carry out an empirical association study on the problem of market value relevance of consolidated financial statements and of individual financial statements of the parent company, searching for an answer to the above question. In this sense, we analyze the (absolute and relative) market value relevance of consolidated accounting information of listed companies between 2003-2008 on the largest stock markets in Europe (London, Paris, and Frankfurt). Through this empirical study we intend to contribute to the relatively limited literature on this topic with a comparative time analysis of the absolute and incremental relevance of financial information supplied by the two categories of financial statements (group and individual).
Keywords: M41; F23; G34; G15; 650; Consolidated Financial Statements; Parent Company Financial Statements; Market Value Relevance